Hubungan antara Happiness dengan Fear of Missing Out pada Dewasa Awal Pengguna Media Sosial di NTT - Saekoko, Priska P. M; Arianti, Rudangta (Kajian Psikologi dan Kesehatan Mental, 2024)
Purpose: The purpose of this study was to determine whether there is a relationship between happiness and FoMO in early adult social media users in NTT. Research methodology: This study used quantitative research methods with non-linear regression design. The study participants were 212 early adult men and women with an age range of 18-40 years who lived in NTT and were active on one social media or even more than one with a minimum period of 3 hours a day. Results: The results of the non-linearity regression test using the "Quadratic" method obtained a value of b = -1.736 and P = 0.028 (P<0.05) which is therefore a significant negative relationship between happiness and FoMO in early adult social media users in NTT. Conclusions: There is a U-shaped negative relationship between happiness and FoMO among young adults in NTT. The lowest FoMO occurs at a moderate level of happiness, which aligns with the respondents’ condition. Limitations: From the results of the research and discussion conducted, it can be concluded that early adult social media users in NTT who are respondents in this study need to increase happiness to be wiser in using social media so as not to experience FoMO. When early adulthood in NTT does not feel life satisfaction or experience anxiety, you should look for something else that can make early adult individuals in NTT accept themselves and their environment instead of using excessive social media, because it will have the potential for early adulthood to experience FoMO Contribution: This research is expected to help early adults in NTT to improve and direct their feelings of happiness, so that early adults in NTT can regulate behavior in social media besides that it can reduce the tendency to experience FoMO.